Cluster type strain clamp and preparation method thereof

By using weather-resistant glass fiber reinforced nylon composite material and modified nano-silica, combined with the "z" font crimp structure, the problem of mechanical strength reduction of traditional bundled tension wire clips under high humidity environment is solved, and the mechanical strength of traditional bundled tension wires is reduced in environments with high humidity is achieved. Long service life and higher wire grip.

CN119209361APending Publication Date: 2024-12-27HONGQI GRP ELECTRIC POWER FITTINGS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411417846.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The mechanical strength of the traditional cluster tension wire clip is reduced in environments with high humidity, and its service life is short, which cannot meet the improvement of rural power grid electricity demand.

Method used

Weather-resistant glass fiber reinforced nylon composite material is used to modify and add modified nanosilicon dioxide through glass fiber surface modification to improve the tensile strength, bending strength and notch-free impact strength of the material, and adopt the "z" font crimping structure to Enhance wire grip.

Benefits of technology

It significantly improves the mechanical properties and service life of the material, can maintain good mechanical strength in high humidity environments, and meets the improvement of electricity demand for rural power grids.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119209361A_ABST
    Figure CN119209361A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electric power fittings in an electric power system, in particular to a cluster type strain clamp and a preparation method thereof.The cluster type strain clamp comprises a strain clamp body, the strain clamp body comprises a wedge plate, lower covers are arranged on the two sides of the wedge plate respectively, and an upper cover is arranged on the side, away from the wedge plate, of each lower cover; the upper cover and the lower cover are both made of a weather-resistant glass fiber reinforced nylon composite material through injection molding, and the weather-resistant glass fiber reinforced nylon composite material is prepared from the following raw materials in percentage by weight: 35-45% of glass fiber, 0.3-0.5% of an anti-ultraviolet aid, 0.3-0.5% of an antioxidant, 5-6% of a flexibilizer, 0.05-0.15% of a lubricant, 0-3% of color master batch, 0.1-0.3% of a coupling agent, 0.05-0.15% of a heat stabilizer and the balance of PA66. The method has the advantage that the weather resistance of the cluster type strain clamp is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of power fittings in power systems, and in particular to a clustered tension clamp and a preparation method thereof. Background Art

[0002] The clustered type tension clamp is a device for fixing parallel clustered overhead insulated cables. Among them, the parallel clustered conductors are powered by three-phase four-wires, which reduces the imbalance of the three-phase load of the distribution transformer to a minimum, reduces the neutral line current, and thus reduces the resistance loss. It is widely used in rural power grid transformation. Due to the use of a compact symmetrical split structure, the inductance of the conductor is reduced, the dielectric constant between the lines is increased, the capacitance is increased, and the circuit reactance is greatly reduced, ultimately achieving the purpose of capacity expansion and loss reduction. Traditional parallel clustered overhead insulated cables use small square conductors, but in recent years, the power consumption of rural power grids has increased sharply, and it is necessary to increase the cross-sectional area of ​​the conductors and increase the current carrying capacity of the conductors. At the same time, the clustered type tension clamps are also required to have higher gripping force. Traditional clustered type tension clamps usually use ordinary engineering plastics, which have low weather resistance. Especially when the humidity is high, its mechanical strength decreases greatly, which makes the service life of the tension clamps short. Summary of the invention

[0003] In order to improve the weather resistance of a clustered type tension clamp, the present application provides a clustered type tension clamp and a preparation method thereof.

[0004] In the first aspect, the present application provides a clustered tension clamp, which adopts the following technical solution: A clustered tension clamp comprises a tension clamp body, the tension clamp body comprises a wedge plate, lower covers are respectively arranged on both sides of the wedge plate, an upper cover is arranged on the side of the lower cover away from the wedge plate, the upper cover and the lower cover are both injection-molded from a weather-resistant glass fiber reinforced nylon composite material, and the weather-resistant glass fiber reinforced nylon composite material is made of raw materials with the following percentages: glass fiber 35-45%, anti-ultraviolet additive 0.3-0.5%, antioxidant 0.3-0.5%, toughening agent 5-6%, lubricant 0.05-0.15%, masterbatch 0-3%, coupling agent 0.1-0.3%, heat stabilizer 0.05-0.15%, and the balance is PA66.

[0005] By adopting the above technical scheme, the tensile strength of the weather-resistant glass fiber reinforced nylon composite material prepared in this application can reach 180MPa and the flexural strength can reach 260MPa by selecting the basic raw materials and adjusting the dosage. At the same time, the unnotched impact strength can reach 95KJ / m 2 , placed in an environment of 25℃ and 50% relative humidity for 960h, its tensile strength can still reach 147MPa, its flexural strength can still reach 240MPa, and its unnotched impact strength can still reach 79KJ / m 2Its mechanical strength is still good after the moisture absorption test, and the clustered tension clamp used to prepare it can have a longer service life.

[0006] Preferably, the glass fiber is a modified glass fiber, and the modification method is as follows: the surface of the glass fiber is coupled with an aminosilane coupling agent, and then condensed with a dibasic fatty acid to obtain the modified glass fiber.

[0007] By adopting the above technical solution, the glass fiber plays a supporting role of the skeleton in the system. The moisture absorption of the material in the environment weakens the interface bonding effect between the glass fiber and the nylon molecular material. Under the action of external force, the glass fiber and the nylon polymer material are blocked, resulting in a significant reduction in the mechanical properties of the glass fiber reinforced nylon composite material, which cannot meet the requirements for continued work. By surface modification of the glass fiber, the compatibility between the glass fiber and the system can be increased, the interfacial tension between the glass fiber and the system can be greatly reduced, and the bonding force between the glass fiber and the nylon polymer material can be enhanced, which can greatly improve the mechanical properties of the glass fiber reinforced nylon composite material and extend its life.

[0008] Preferably, the weather-resistant glass fiber reinforced nylon composite material further comprises 2-4% hydroxylated nano-silicon dioxide.

[0009] By adopting the above technical solution and adding a certain amount of hydroxylated nano-silica, the mechanical strength of the glass fiber reinforced nylon composite material can be improved.

[0010] Preferably, the hydroxylated nano-silica is modified by hydrolyzing maleic anhydride and dibasic fatty acid by grafting hydroxyl groups on the surface.

[0011] By adopting the above technical scheme, the surface polarity of hydroxylated nano-silica is modified, and aliphatic hydrocarbon diacids and hydrolyzed maleic anhydride are grafted on its surface. After adding the modified nano-silica, the molecules grafted on its surface and the molecules grafted on the surface of the glass fiber can be cross-linked, so that the glass fiber reinforced nylon composite material has a network structure inside, and the nano-silica and glass fiber serve as the skeleton of the network structure, so that the glass fiber reinforced nylon composite material has higher integrity; in addition, it is speculated that the cross-linked structure increases the number of nano-silica particles around the glass fiber, making it difficult for the nylon molecules around it to combine with water molecules entering from the outside due to steric hindrance; under the action of these two aspects, the mechanical properties of the glass fiber reinforced nylon composite material after the moisture absorption test are greatly improved, and its weather resistance is excellent.

[0012] Preferably, the dibasic fatty acid is one or both of dodecanedioic acid and hexadecanedioic acid.

[0013] By adopting the above technical scheme, a weather-resistant glass fiber reinforced nylon composite material with excellent mechanical properties can be prepared by using one or both of dodecanedioic acid and hexadecanedioic acid as binary fatty acids.

[0014] Preferably, the weather-resistant glass fiber reinforced nylon composite material further comprises 2-4% hydroxylated nano-silicon dioxide, and the hydroxylated nano-silicon dioxide is modified by grafting hydrolysis of maleic anhydride and dibasic fatty acid on the surface of the hydroxyl group.

[0015] By adopting the above technical solution and adding a certain amount of hydroxylated nano-silica, the mechanical strength of the glass fiber reinforced nylon composite material can be improved. Surface modification can increase the compatibility between the nano-silica and the system, improve its bonding strength with the system, and further improve the weather-resistant glass fiber reinforced nylon composite material.

[0016] Preferably, the glass fiber has a diameter of 4-6 μm and a length of 0.6-0.8 mm.

[0017] Preferably, the particle size of the hydroxylated nano-silica is 30-50 nm.

[0018] Preferably, the tension clamp body adopts a Z-shaped wire pressing structure.

[0019] By adopting the above technical solution, the tension clamp body adopts a "z"-shaped wire pressing structure, which improves the conductor gripping force through secondary conductor deformation.

[0020] In a second aspect, the present application provides a method for preparing a clustered tension clamp, which adopts the following technical solution: A method for preparing a clustered tension clamp comprises the following steps: S1, granulation: mix and granulate the raw materials, the extrusion temperature is 240-270℃, and the screw is extruded and granulated to obtain masterbatch; S2, drying: drying the masterbatch obtained in S1, the drying temperature is 70-90°C, and the drying time is 3-5h; S3, injection molding: melting temperature is 275-305℃, barrel constant temperature is 230-250℃, mold temperature is 75-90℃; S4. Humidity adjustment: water temperature is 90-100℃, humidity adjustment time is 2.5-4h.

[0021] By adopting the above technical scheme, the method for preparing the weather-resistant glass fiber reinforced nylon composite material of the present application does not require special equipment, nor does it require improvement of the equipment. It has a high tolerance for production process parameters, has a high qualified rate of the prepared products, and is suitable for large-scale production.

[0022] In summary, the present application includes at least one of the following beneficial technical effects: 1. The tensile strength of the weather-resistant glass fiber reinforced nylon composite material prepared in this application can reach 180MPa and 260MPa by adjusting the selection and dosage of the basic raw materials. At the same time, the unnotched impact strength can reach 95KJ / m 2 , placed in an environment of 25℃ and 50% relative humidity for 960h, its tensile strength can still reach 147MPa, its flexural strength can still reach 240MPa, and its unnotched impact strength can still reach 79KJ / m 2 Its mechanical strength is still good after the moisture absorption test, and the clustered tension clamp used to prepare it can have a longer service life.

[0023] 2. The tensile strength of the weather-resistant glass fiber reinforced nylon composite material prepared in this application can reach 180MPa and 260MPa by selecting the basic raw materials and adjusting the dosage. At the same time, the unnotched impact strength can reach 95KJ / m 2 ; and by modifying the surface of the glass fiber and adding modified nano-silica, the tensile strength of the glass fiber reinforced nylon composite material can be further increased to 225MPa, the flexural strength can be further increased to 298MPa, and the unnotched impact strength can be further increased to 115MPa; it can be seen that the weather-resistant glass fiber reinforced nylon composite material prepared in the present application has excellent mechanical properties and its strength is greatly improved. It can be used in tension clamps to fully meet the use requirements.

[0024] Reference numerals Figure 1 It is a schematic structural diagram of a clustered type tension clamp according to an embodiment.

[0025] Figure 2 It is a schematic diagram of the cross-sectional structure of the upper cover.

[0026] Figure 3 It is a schematic diagram of the cross-sectional structure of the lower cover.

[0027] Figure 4 It is a schematic diagram showing the structure of the wedge plate.

[0028] Figure 5 It is a schematic diagram of the structure of the "Z"-shaped pressure wire of the tension clamp body.

[0029] Explanation of the reference numerals: 1. tension clamp body; 2. wedge plate; 21. pull rod; 22. bump; 3. lower cover; 4. upper cover; 5. wire groove; 51. anti-slip marking line; 52. wire outlet; 6. metal cover; 7. connecting bolt. DETAILED DESCRIPTION

[0030] The present application is further described in detail below in conjunction with the specific contents.

[0031] raw material Among the raw materials used in this application, PA66 is industrial grade; the diameter of the glass fiber is 4-6μm and the length is 0.6-0.8mm; the particle size of hydroxylated nano-silica is 30-50nm; the coupling agent is KH-171; the model of the thermal stabilizer is 1076; the average molecular weight of hydrolyzed polymaleic anhydride is 400-800; the remaining raw materials are common commercial products, and the purity of the chemical products involved is analytical grade. Example

[0032] Example 1 A cluster type tension clamp, such as Figure 1 As shown, the tension clamp body 1 includes a wedge plate 2, and a pull rod 21 is bolted to the wedge plate 2. Lower covers 3 are respectively arranged on both sides of the wedge plate 2, and an upper cover 4 is arranged on the side of the lower cover 3 away from the wedge plate 2. Figure 2 and Figure 3 As shown, two wire grooves 5 are arranged on the sides of the upper cover 4 and the lower cover 3 that are close to each other, and the surfaces of the wire grooves 5 are arranged with anti-skid engraved lines 51. And the anti-skid engraved lines 51 of the upper cover 4 and the lower cover 3 are staggered and alternate.

[0033] like Figure 1 As shown, a groove is provided on the side of the upper cover 4 away from the wedge plate 2, and a metal cover 6 is inserted into the groove. The two metal covers 6 are fixed by connecting bolts 7, and the connecting bolts 7 pass through the upper cover 4, the lower cover 3 and the wedge plate 2 at the same time.

[0034] When installing the tension clamp body 1, remove the upper cover 4, and then place the bundled wires in the wire grooves 5 on the lower cover 3, and then cover the upper cover 4. The wires are bound between the upper cover 4 and the lower cover 3 through the wire grooves 5, and then install the connecting bolts 7 to fix the bundled wires on the tension clamp body 1. The anti-slip engraved lines 51 of the upper cover 4 and the lower cover 3 are staggered and alternate, which can increase the grip on the wires.

[0035] like Figure 3 As shown, a plurality of limiting protrusions 22 are arranged on the surface of the wedge plate 2 close to the lower cover 3, and a limiting groove (not shown) corresponding to the position of the limiting protrusion 22 is arranged on one side of the lower cover 3 close to the wedge plate 2. When installing the lower cover 3, the limiting protrusion 22 is correspondingly plugged into the limiting groove, which can realize the position limitation of the lower cover 3 and make the installation more accurate. The number of parts of the tension clamp body 1 is reduced, the structure is optimized, the installation is simple, and the phenomenon of falling during high-altitude operations can be reduced.

[0036] like Figure 2 and Figure 3 As shown, both ends of the wire slot 5 are wire outlets 52, and the shape of the wire outlet 52 is designed to be an arc, and the shape of the arc can reduce the wear on the wire.

[0037] like Figure 4 As shown, the angle of the wedge plate 2 is 7-9 degrees higher than that of the conventional one. During long-term operation, the bolt torque decreases due to material creep, and the angle of the wedge plate 2 increases, which can improve the conductor grip.

[0038] like Figure 5 As shown, the tension clamp body 1 adopts a "z"-shaped wire pressing structure, which improves the wire gripping force through secondary wire deformation.

[0039] Among them, the upper cover 4 and the lower cover 3 of the tension clamp body 1 are both injection molded by weather-resistant glass fiber reinforced nylon composite material. The raw materials and the amounts of the weather-resistant glass fiber reinforced nylon composite material are shown in Table 1. The preparation method is as follows: S1, granulation: the raw materials are mixed and granulated, wherein the extruder screw speed is 200r / min, the feed speed is 10r / min, the extrusion temperature is 240-270°C, and the screw is extruded and granulated to obtain a masterbatch; S2, drying: drying the masterbatch obtained in S1 at a drying temperature of 80°C for 3-4 hours; S3, injection molding: melting temperature is 275-305℃, barrel constant temperature is 240℃, mold temperature is 80℃, and other process parameters are as follows: S4. Humidity adjustment: water temperature is 90-100℃, humidity adjustment time is 3h.

[0040] Table 1 Raw materials and amounts of raw materials in Example 1 (kg) PA66 51.2 Anti-ultraviolet additive uv-5 0.4 Antioxidant A168 0.2 Antioxidant B1010 0.2 Toughening agent ST-6 5.6 Lubricant PE wax 0.1 Fiberglass 40 Aniline Black 2 Coupling agent 0.2 Heat Stabilizer 0.1 Example 2 A clustered tension clamp, which is different from Example 1 in that the raw glass fiber in the weather-resistant glass fiber reinforced nylon composite material is surface-modified by the following method, and the modification method is as follows: S1. Dissolve γ-aminopropyltriethoxysilane in anhydrous ethanol to obtain methylvinyldimethoxysilane ethanol solution. Add glass fiber and place the mixture in a high-speed stirrer. Stir for 5 minutes, filter and dry at 50°C. Wherein, the γ-aminopropyltriethoxysilane ethanol solution is a saturated solution, and the weight ratio of the methylvinyldimethoxysilane ethanol solution to the glass fiber is 1.5:10; S2. Disperse 1 g of dodecanedioic acid in 300 mL of N,N-dimethylformamide, then add 5 g of HOBT and 4 g of EDC·HCl, stir for 40 min, add 10 mL of triethanolamine, stir for 10 min, add 5 g of the treated glass fiber prepared in S1, stir and react at 25°C for 12 h. After the reaction is completed, filter, wash the precipitate with DMF and ethanol in turn, and then dry to obtain modified glass fiber.

[0041] Example 3 A clustered tension clamp is different from Example 2 in that the raw materials of the weather-resistant glass fiber reinforced nylon composite material also include 3 kg of hydroxylated nano-silica, the added amount of PA66 is 48.2 kg, and the remaining steps are the same as Example 2.

[0042] Example 4 A cluster-type tension clamp, which is different from Example 3 in that, in the raw materials of its weather-resistant glass fiber reinforced nylon composite material, hydroxylated nano-silica is replaced by modified nano-silica, and the preparation method of the modified nano-silica is as follows: 5 g of hydroxylated nano-silica, 1.0 g of hydrolyzed maleic anhydride and 3.5 g of dodecanedioic acid are added to 200 mL of DMF, the temperature is raised to 75°C, the reaction is stirred for 12 hours, filtered, washed with DMF and ethanol, and dried at 70°C to obtain modified nano-silica.

[0043] Example 5 A clustered tension clamp is different from Example 4 in that, in the raw materials of the weather-resistant glass fiber reinforced nylon composite material, the dodecanedioic acid used in the preparation of the modified glass fiber is replaced by hexadecanedioic acid, and the remaining steps are the same as Example 4.

[0044] Example 6 A clustered tension clamp is different from Example 4 in that, in the raw materials of the weather-resistant glass fiber reinforced nylon composite material, the dodecanedioic acid used in the preparation of the modified nano-silica is replaced by hexadecanedioic acid, and the remaining steps are the same as Example 4.

[0045] Example 7 A clustered tension clamp is different from Example 4 in that the amount of modified nano-silicon dioxide added to the raw materials of the weather-resistant glass fiber reinforced nylon composite material is 2 kg, and the amount of PA66 added is 49.2 kg, and the remaining steps are the same as Example 4.

[0046] Example 8 A clustered tension clamp is different from Example 4 in that, in the raw materials of the weather-resistant glass fiber reinforced nylon composite material, the added amount of modified nano-silicon dioxide is 4 kg, and the added amount of PA66 is 49.2 kg, and the remaining steps are the same as Example 4.

[0047] Example 9 A clustered tension clamp is different from Example 4 in that the modified glass fiber in the raw material of the weather-resistant glass fiber reinforced nylon composite material is replaced with glass fiber of equal mass, and the remaining steps are the same as Example 4.

[0048] Example 10 A clustered tension clamp is different from Example 4 in that, in the raw materials of the weather-resistant glass fiber reinforced nylon composite material, the hydrolyzed maleic anhydride is replaced by an equal mass of dodecanedioic acid during the preparation of the modified nano-silica, and the remaining steps are the same as Example 4.

[0049] Comparative Example Comparative Example 1 A clustered tension clamp is different from Example 4 in that, in the raw material of the weather-resistant glass fiber reinforced nylon composite material, modified nano-silica is prepared using hydroxylated silica, and the remaining steps are the same as Example 4.

[0050] Performance testing Detection method / test method Weather-resistant glass fiber reinforced nylon composite materials were prepared according to the preparation methods of Examples 1-10 and Comparative Example 1, and then tested according to the following testing methods. The test results are shown in Table 2.

[0051] Tensile strength: tested according to the method in GB / T1040, sample size is 150mm×10mm×4mm, tensile strength is 50mm / min; Bending strength: tested according to the method in GB / T9341, sample size is 80mm×10mm×4mm, speed is 2mm / min; Unnotched impact strength: tested according to the method in GB / T1043, with a sample size of 80mm×10mm×4mm; Water absorption experiment: the prepared weather-resistant glass fiber reinforced nylon composite material samples were placed statically and without stacking under a standard environment of temperature 25°C and relative humidity 50% for 960 hours. After the placement, the tensile strength, flexural strength and unnotched impact strength were tested according to the above-mentioned test methods.

[0052] Table 2 Test results of Examples 1-10 and Comparative Example 1 It can be seen from the test data of Examples 1-10 and Comparative Example 1, as well as Table 2, that the tensile strength of the weather-resistant glass fiber reinforced nylon composite material prepared in the present application can reach 180 MPa and the flexural strength can reach 260 MPa by selecting the basic raw materials and adjusting the dosage. At the same time, the unnotched impact strength can reach 95 KJ / m 2; and by modifying the surface of the glass fiber and adding modified nano-silica, the tensile strength of the glass fiber reinforced nylon composite material can be further increased to 225MPa, the flexural strength can be further increased to 298MPa, and the unnotched impact strength can be further increased to 115MPa; it can be seen that the weather-resistant glass fiber reinforced nylon composite material prepared in the present application has excellent mechanical properties and its strength is greatly improved. It can be used in tension clamps to fully meet the use requirements.

[0053] As nylon is a polar polymer material, the amide groups in its molecular structure have very strong water absorption. It is very easy to be affected by the humidity of the environment during use. The hydrogen bonds between its molecules interact with the moisture in the environment. As the water molecules continue to accumulate and diffuse into the material, the gaps between the molecules of the nylon material can increase, or even degrade. Glass fiber plays a supporting role in the system. The moisture absorption of the material in the environment weakens the interface bonding between the glass fiber and the nylon molecular material. Under the action of external force, the glass fiber and the nylon polymer material are fused, resulting in a significant reduction in the mechanical properties of the glass fiber reinforced nylon composite material, which cannot meet the requirements for continued work.

[0054] By surface modifying the glass fiber, the compatibility between the glass fiber and the system can be increased, the interfacial tension between the glass fiber and the system can be greatly reduced, the bonding force between the glass fiber and the nylon polymer material can be enhanced, and the mechanical properties of the glass fiber reinforced nylon composite material can be greatly improved and its life can be extended. It can also be seen from the test data of Example 1 and Example 2 that after the glass fiber is surface modified, the tensile strength, flexural strength and unnotched impact strength of the glass fiber reinforced nylon composite material are all improved to a certain extent, and after the water absorption experiment, its mechanical properties are also improved.

[0055] It can be seen from the test data of Examples 2-3 that, on the basis of modifying the glass fiber, the present application continues to add a certain amount of hydroxylated nano-silica, which can improve the mechanical strength of the glass fiber reinforced nylon composite material. However, due to moisture absorption, the bonding force between the surface of the hydroxylated nano-silica and the nylon material becomes poor. After the water absorption test, the mechanical strength of the glass fiber reinforced nylon composite material decreases significantly.

[0056] Continue to modify the surface polarity of hydroxylated nano-silica, so that its surface is grafted with aliphatic hydrocarbon diacid and hydrolyzed maleic anhydride. After adding modified nano-silica, the molecules grafted on its surface and the molecules grafted on the surface of glass fiber can be cross-linked, so that the glass fiber reinforced nylon composite material has a mesh structure inside, and nano-silica and glass fiber serve as the skeleton of the mesh structure, so that the glass fiber reinforced nylon composite material has higher integrity; in addition, it is speculated that the cross-linked structure increases the number of nano-silica particles around the glass fiber, making it difficult for the nylon molecules around it to combine with the water molecules entering from the outside due to steric hindrance; under the action of these two aspects, the mechanical properties of the glass fiber reinforced nylon composite material after the moisture absorption experiment are greatly improved, and its weather resistance is excellent. This can be verified by combining the test data of Examples 2-6 and Example 9. Through Examples 7-8, it can be seen that when the addition amount of modified nano-silica is 4%, the mechanical strength and water resistance of the glass fiber reinforced nylon composite material are better, but combined with the production cost, the improvement is lower than that when the addition amount is 3%. On the whole, when the addition amount of modified nano-silica is 3%, it is more economical.

[0057] It can be seen from the test data of Example 4 and Example 10 that the molecular structure grafted on the surface of modified nano-silica is the key to affecting the cross-linking effect, and the molecule needs to contain a certain amount of hydrolyzed maleic anhydride molecular chain to achieve the expected cross-linking effect.

[0058] It can be seen from the test data of Example 4 and Comparative Example 1 that when silicon dioxide is non-nano materials, the technical effect of the present application cannot be achieved. This is because its particles are larger. On the one hand, due to the larger contact surface between it and the system, the interfacial tension is larger. After absorbing moisture, the peeling effect between it and the system is stronger, making the integrity of the composite material insufficient; on the other hand, the cross-linking effect between it and the modified glass fiber becomes worse. Therefore, the present application is more suitable for nano materials as raw materials.

[0059] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. A cluster type tension clamp, characterized in that: The invention comprises a tension clamp body (1), the tension clamp body (1) comprising a wedge plate (2), lower covers (3) being respectively arranged on both sides of the wedge plate (2), an upper cover (4) being arranged on the side of the lower cover (3) away from the wedge plate (2), the upper cover (4) and the lower cover (3) being both injection-molded from a weather-resistant glass fiber reinforced nylon composite material, the weather-resistant glass fiber reinforced nylon composite material being made from raw materials having the following percentage contents: 35-45% glass fiber, 0.3-0.5% anti-ultraviolet additive, 0.3-0.5% antioxidant, 5-6% toughening agent, 0.05-0.15% lubricant, 0.05-0.15% masterbatch, 0.1-0.3% coupling agent, 0.05-0.15% heat stabilizer, and the balance being PA66.

2. A cluster type tension clamp according to claim 1, characterized in that: The glass fiber is a modified glass fiber, and the modification method thereof is as follows: the surface of the glass fiber is coupled by an aminosilane coupling agent, and then condensed with a dibasic fatty acid to obtain the modified glass fiber.

3. A cluster type tension clamp according to claim 2, characterized in that: The weather-resistant glass fiber reinforced nylon composite material also includes 2-4% of hydroxylated nano-silicon dioxide.

4. A clustered tension clamp according to claim 3, characterized in that: The hydroxylated nano-silicon dioxide is modified by hydrolyzing maleic anhydride and dibasic fatty acid through grafting of hydroxyl groups on the surface.

5. The cluster type tension clamp according to claim 2, characterized in that: The dibasic fatty acid is one or both of dodecanedioic acid and hexadecanedioic acid.

6. The cluster type tension clamp according to claim 1, characterized in that: The weather-resistant glass fiber reinforced nylon composite material also includes 2-4% of hydroxylated nano-silicon dioxide, and the hydroxylated nano-silicon dioxide is modified by hydrolyzing maleic anhydride and dibasic fatty acid through grafting of hydroxyl groups on the surface.

7. The cluster type tension clamp according to claim 1, characterized in that: The glass fiber has a diameter of 4-6 μm and a length of 0.6-0.8 mm.

8. The clustered tension clamp according to any one of claims 3, 4 and 6, characterized in that: The particle size of the hydroxylated nano-silicon dioxide is 30-50 nm.

9. The cluster type tension clamp according to any one of claims 1 to 7, characterized in that: The tension clamp body (1) adopts a Z-shaped wire pressing structure.

10. A method for preparing the clustered tension clamp according to any one of claims 1 to 7, characterized in that: It includes the following steps: S1, granulation: mix and granulate the raw materials, the extrusion temperature is 240-270℃, and the screw is extruded and granulated to obtain masterbatch; S2, drying: drying the masterbatch obtained in S1, the drying temperature is 70-90°C, and the drying time is 3-5h; S3, injection molding: melting temperature is 275-305℃, barrel constant temperature is 230-250℃, mold temperature is 75-90℃; S4. Humidity adjustment: water temperature is 90-100℃, humidity adjustment time is 2.5-4h.